CITRA PEREMPUAN DALAM CERPEN SUATU HARI DI BULAN DESMBER 2002 KARYA SAPARDI DJOKO DAMONO DAN DONGENG SEBELUM BERCINTA KARYA EKA KURNIAWAN - Manyu Santoso (RUANG KATA: Journal of Language and Literature Studies, 2022)
As a form of concern for women, especially in the literary field, researchers are interested in analyzing the short story entitled One Day in December 2002 by Sapardi Djoko Damono and the short story Fairy Tale Before Sleeping by Eka Kurniawan. This study aims to reveal the image of women in the short story One Day in December 2002 by Sapardi Djoko Damono and the short story Fairy Tale Before Sleeping by Eka Kurniawan. To support this research, the researcher conducted a structural analysis to find supporting data in revealing the image of women in the short story. The approach in this research is a liberal feminist approach. The results of this study are, 1) The short stories One Day in December 2002 and the Fairy Tale Before Bercita have the theme of problems that occur in domestic life, but there are differences in the two short stories which are the source of the problem. 2) The setting in both short stories takes the background of a husband and wife's life, the difference between the two short stories is the age of their marriage. 3) The characters and characterizations in the two short stories are divided into two, namely the main character and the supporting character. The main character in the short story One Day in December 2002 is Marsiyam and the main character in the short story Fairy Tale Before Making Love is Alamanda. 4) the image of women who dominate men is depicted through the activities or treatment carried out by the female characters. 5) the image of a woman who is smart and clever is depicted through the mindset of the female character. In the builders of the two short stories, One Day in December 2002 and the Fairy Tale Before Making Love, they are the theme, setting, and characterizations. Furthermore, the image of women that breaks the objectivity of women in the poems One Day in December 2002 and the Fairy Tale Before Making Love, namely, the image of women who dominate men and the image of women who are smart and intelligent. Keywords : image, women, feminism